2002
DOI: 10.1076/phbi.40.2.107.5838
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Scavenging Activities of Flavonoid Extract (Kolaviron) of Garcinia kola Seeds

Abstract: The antioxidant and scavenging properties of kolaviron, a flavonoid extract of Garcinia kola seeds, were evaluated in a series of in vitro assays involving free radicals and reactive oxygen species. Kolaviron exhibited markedly reducing power and antioxidant activity by inhibiting the peroxidation of linoleic acid. Kolaviron exhibited 57% scavenging effect on superoxide at a concentration of 1 mg/ml and 85% scavenging effect on hydrogen peroxide at a concentration of 1.5 mg/ml. Similarly, kolaviron, at a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…These two types differ morphologically and biochemically [8][9][10][11] . Accidental cell death is regarded as necrotic and could result from extrinsic insults to the cell such as osmotic, thermal, toxic and traumatic effects [11][12][13] . Pathological cell death is regarded as apoptotic and is an organized programmed cell death (PCD) that is mediated by active and intrinsic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These two types differ morphologically and biochemically [8][9][10][11] . Accidental cell death is regarded as necrotic and could result from extrinsic insults to the cell such as osmotic, thermal, toxic and traumatic effects [11][12][13] . Pathological cell death is regarded as apoptotic and is an organized programmed cell death (PCD) that is mediated by active and intrinsic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids present in plants are known to have numerous beneficial pharmacological effects 8 . Some bioflavonoids have been reported to possess antioxidant properties which help to combat free radical induced oxidative stress 15 . Results from the acute toxicity test of the ethanol extract of the plant (Table 2) show that the plant has no toxic effect on the animal (LD 50 > 5g/kg body weight).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds of bitter kola are highly valued for its stimulating effects (Atawodi, Mende, Pfundstein, Preussmann, & Spiegelhalder, 1995). Bitter kola seed is used broadly in African folklore as therapeutic interventions for diverse diseases (Farombi, Akanni, & Emerole, 2002; Onunkwo, Egeonu, Adikwu, Ojile, & Alowosulu, 2004), such as for treatment of cough, as antipurgative and as aphrodisiac (Madubunyi, 1995; Okunji & Iwu, 1991). Studies showed that predominant phytochemicals in bitter kola seed includes saponin, tannin, and oxalates among others.…”
Section: Introductionmentioning
confidence: 99%